Comparison of 3D Printing Technologies for Polymer-HA Bone Scaffolds: A Systematic Review Toward Hybrid Fabrication Strategies - Kumarajati, Dhananjaya Yama Hudha; Herianto; Herliansyah, Muhammad Kusumawan; Kusmono; Tontowi, Alva Edy (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2025)
Bone scaffold fabrication using 3D printing faces a fundamental dilemma: the trade-off between mechanical strength and biological functionality. To address this challenge, a systematic literature review (SLR) of 28 primary research articles was conducted to compare various hydroxyapatite-based scaffold fabrication technologies. The analysis confirms a clear trade-off: Fused Filament Fabrication (FFF) excels in mechanical strength, Digital Light Processing (DLP) in architectural precision (<100 µm), and Direct Ink Writing (DIW) in flexibility for bio-functionality, proving no single method is ideal. The main conclusion is that hybrid fabrication strategies—intelligently integrating the strengths of multiple technologies—offer the most promising approach to creating functional scaffolds with an optimal balance of strength and bioactivity for future clinical applications.